Establishment of a participatory framework for the training of professionals with the ICESI university. - Jimenez, Daniel; Muñoz, Luis Armando (2023)
This product refers to the design of a diploma course, developed together with a national private university, the diploma course seeks to update professionals in the agri-food sector, in the face of digital technologies with a focus on climate change, gender and transformation of agro-food systems.